Experiences of students with disabilities during the covid-19 pandemic: challenges and opportunities for learning - Cotán Fernández, Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The pandemic caused by covid-19 has altered all sectors of society worldwide. In the case of this article, the changes caused in the educational field will be addressed, specifically in Higher Education institutions. To do this, the main objective pursued in this study is to analyze the facilitators and obstacles that students with disabilities identified during the first two pandemic courses. To this end, the experiences of three students with disabilities will be analyzed. From a case study approach, the semi- structured interview has been the information collection instrument. The results obtained pose numerous challenges and opportunities to develop online educational processes that are accessible and equitable for the entire student group.